Impact of Crude Price Volatility on Levels of Economic Activity: Evidence from Iraq - Al-Zanganee, Shlair Abdulkhaleq Mohammed (European Scientific Journal, ESJ, 2017)
Global oil markets witnessed intense price volatility in the recent years. Volatility of crude oil price is perceived as a significant source of economic fluctuation. It could likely affect levels of economic activities whether in oil exporting or in oil importing economies. The following study proves that the impact of oil price shocks is not exclusive to oil importing economies. Iraq's developing economy which is highly dependent on oil exports as a main source of revenues is vulnerable to oil price shocks. This study employs a multivariate autoregressive regression (VAR) model to investigate the impact of crude oil price volatility on levels of economic activity in Iraq. The time series datasets employed in the study are tested for stationarity and co-integration using the augmented Dickey-Fuller (ADF) unit root test and Johansen test for cointegration respectively. The model’s results confirmed the highly significant impact of volatility of crude oil price on levels of GDP in Iraq.